Scholarly Teaching Through Action Research: A Narrative of One Professor's Process - Jana Hunzicker (Park University, 2016)
This article shares a first-hand account of an action research project conducted in a college-level early adolescent development course to better understand written and verbal reflection as learning tools, improve the author's teaching effectiveness, and foster reflective habits in pre-service teachers. The article includes a brief overview of related literature and a description of several reflective activities and assignments used in the course before presenting and discussing the project's results based on Ferrance's (2000) 6-step action research process.